Produção da nucleoproteína recombinante do vírus da influenza aviária para aplicação no imunodiagnóstico - Borzi, Mariana Monezi [UNESP] (2015)
The nucleoprotein (NP) of Avian Influenza Virus (AIV) is an important antigenic target for immunodiagnosis of this disease, due to its low variability among different AIV strains, resulting in high cross-reactivity, and the also highly immunogenic for vertebrate hosts. In this study, the gene enconding NP of AIV was cloned and expressed in Escherichia coli as a recombinant protein fused to SUMO polypeptide with a polyhistidine tag and used to develop an indirect ELISA for the detection of AIV-specific antibodies. The recombinant NP was expressed in the soluble fraction and easily purified. After Analysis of the main sites of antigenicity and characterization in Western-Blotting, the recombinant NP was optimized as an antigen preparation for indirect ELISA to detect anti-AIV antibodies in chicken serum samples. The comparative analysis of this ELISA with a commercial ELISA showed values of 95%, 97%, 96.7% of sensitivity, specificity and accuracy, respectively, and an agreement of k=0.88. In conclusion, the results indicated that the recombinant NP of AIV produced in this study is a good source of antigen for indirect ELISA and provides a sensitive and specific method for the immunodiagnosis of Avian Influenza in chickens